Persepsi Pelanggan terhadap Implementasi Proses Relationship Marketing pada Waroeng Spesial Sambal Yogyakarta - Fakhrudin, Arif (Universitas Muhammadiyah Yogyakarta, 2018)
In modern marketing, paradigm of marketing has shifted, not only to create transaction for reaching success of marketing but company also should interact to customer in long term.The paradigm is called relationship marketing, principle thinking in this practice of marketing is to build closer relationship to create two-way communication in managing benefit relationship between customer and firm.This research measured perception of customer on implementation of process in relationship marketing of Waroeng Spesial Sambal Yogyakarta. Independent variables in this research were relationship marketing input including Understanding Customer Expectation (UCE), Building Service Partnership (BSP), Total Quality Management (TQM), and Empowering Employees (EE).Meanwhile dependent variables in this research were Customer Satisfaction (CS), Customer Loyalty (CL).From Anova test and F test, it could be found that all variables had significant F value of 0.000, so that probability 0.000 was less than significant level of 0.05.It could be concluded that result of all independent variables has effected significantly on all dependent variables.